Fusarium oxysporum f. sp. striga, athletes foot or achilles heel? - Watson, A.; Gressel, J.; Sands, D.; Hallett, S.; Vurro, M.; Beed, Fenton D. (2007)
Parasitic weeds are major contributors to hunger, malnutrition, and food insecurity across sub-Saharan and northern Africa by reducing crop yields in half. Over twenty million hectares of cereal grains in sub-Saharan Africa are infested with Striga (witchweed). Food production losses due to Striga in African countries range from 20% to 90%, amounting to over 10 million tons of food lost annually. The control options for Striga are currently ineffective and management possibilities for these weeds are urgently needed. The research progress with a specific forma specials of Fusarium oxysporum as a biological control for Striga in Africa illustrates the potential to positively impact many lives and improve the health and livelihood of rural and urban poor. Can F. Oxysporum wild type be the Achilles heel of Striga , or do we need enhanced biocontrol to achieve rapid, safe, cost-effective solutions for this major biotic constraint to food production in Africa?